2000
DOI: 10.1076/edre.6.4.281.6934
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Pupils’ Views in Scottish Schools

Abstract: Pupil attitude data have frequently been utilised in school effectiveness and improvement research to examine aspects of a school's educational processes, culture and ethos. However, a related approach is based on the belief that the views and attitudes of pupils are important outcomes of schooling in their own right, in addition to academic or vocational achievement. The rationale for this approach is that schools and teachers can have a positive influence on pupils' attitudes in a range of important areas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Because differences between students within schools are nearly always considerably larger than are differences between schools, the school effects reported in SER studies hardly ever exceed 15% for studies based on achievement scores. For non-cognitive outcomes, the school effects are even smaller (Thomas, Smees, MacBeath, Robertson, & Boyd, 2000;Van der Wal & Rijken, 2002). This does not mean, however, that education makes only a minor contribution to the development of students.…”
Section: The Absolute Effect Of Schoolsmentioning
confidence: 97%
“…Because differences between students within schools are nearly always considerably larger than are differences between schools, the school effects reported in SER studies hardly ever exceed 15% for studies based on achievement scores. For non-cognitive outcomes, the school effects are even smaller (Thomas, Smees, MacBeath, Robertson, & Boyd, 2000;Van der Wal & Rijken, 2002). This does not mean, however, that education makes only a minor contribution to the development of students.…”
Section: The Absolute Effect Of Schoolsmentioning
confidence: 97%
“…In a related study he concludes that a group of disaffected boys can be identified by the end of the primary stages (Tymms, 2001). Thomas et al (2000) report that pupils in Scottish primary schools were also pretty positive in their attitudes and responses to school. They used a 26-item pupil questionnaire which was then reduced through factor analysis to four main areas.…”
Section: Differences In Pupils' Attitudes Between Schoolsmentioning
confidence: 93%
“…Our questionnaire was adapted from previous work undertaken for the Improving School Effectiveness Project (ISEP) based in Scottish primary schools during the midto-late 1990s (see MacBeath & Mortimore, 2001;Thomas et al, 2000). The primary version contained 30 items.…”
Section: The Data and The Samplementioning
confidence: 99%
“…It became clear that some questions were framed wrongly and others were inappropriate, in terms of the construct being measured. Questions that were framed wrongly were reworded, and those questions that appeared to be inappropriate, in terms of that being measured, were reviewed against the types of questioning used in other research projects that also investigated academic engagement, namely those of Lea et al (2003) and Thomas, et al (2000). The final edited version of the questionnaire consisted of twenty one items and was sent via email to respondents during the first week of their long summer vacation requesting that they respond within three weeks.…”
Section: Methodsmentioning
confidence: 99%